2008
DOI: 10.1002/ijc.24097
|View full text |Cite
|
Sign up to set email alerts
|

Circumcision and sexual behavior: Factors independently associated with human papillomavirus detection among men in the HIM study

Abstract: There is growing interest in understanding HPV infection and related disease among men. To date there have been numerous studies reporting HPV DNA prevalence among men from several different countries, however, few have incorporated multivariable analyses to determine factors independently associated with male HPV detection. The purpose of this study was to assess the factors independently associated with HPV detection in men ages 18–70 years residing in Brazil (n=343), Mexico (n=312), and the United States (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 22 publications
(46 reference statements)
8
100
1
5
Order By: Relevance
“…Two prevalence studies with good evidence found a 30% to 40% reduction in risk of infection among circumcised men. 96,97 These studies fail to provide information on the risk of acquiring HPV and may reflect persistence of HPV rather than acquisition of infection. Four studies provide fair evidence that male circumcision protects against HPV.…”
Section: Gonorrheamentioning
confidence: 99%
“…Two prevalence studies with good evidence found a 30% to 40% reduction in risk of infection among circumcised men. 96,97 These studies fail to provide information on the risk of acquiring HPV and may reflect persistence of HPV rather than acquisition of infection. Four studies provide fair evidence that male circumcision protects against HPV.…”
Section: Gonorrheamentioning
confidence: 99%
“…All participants provided written informed consent, and study protocols were approved by institutional review boards at each study site. A more detailed description of the study design and population is reported elsewhere [15,16,17]. The present study includes 2487 men who enrolled in the HIM Study before 1 January 2009, did not have GWs detected at enrollment, and completed at least one 6-month follow-up visit.…”
Section: Study Populationmentioning
confidence: 99%
“…Помимо этого, данная патология на 10% повышает риск преждевременных родов, рождения детей с низкой массой тела и преждев-ременного разрыва плодных оболочек, что в масштабах страны приносит значительный урон и демографической ситуации [19]. Пик инфицирования ВПЧ у женщин прихо-дится на 16-25 лет и снижается с возрастом, у мужчин, напротив, пик пораженности ПВИ приходится на чуть более старший возраст, чем у женщин, и остается посто-янным или незначительно уменьшается по мере взрос-ления [20]. Учитывая высокую распространенность ВПЧ-ассоциированных заболеваний у представителей обоих полов и этические аспекты вакцинации только представителей женского пола, ряд ведущих мировых медицинских организаций, таких как Консультативный комитет по практике иммунизации (Advisory Committee on Immunization Practices, ACIP), Австралийская тех-ническая консультативная группа по иммунизации (Australian Technical Advisory Group on Immunisation, ATAGI), поддерживают гендерно-нейтральный подход к вакцинации против ВПЧ.…”
Section: эпидемиология папилломавирусной инфекции в мире и в россииunclassified